2014
DOI: 10.1155/2014/519035
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Rikkunshito, a Japanese Kampo Medicine, on Gastrointestinal Dysfunction and Anorexia in Combination with Western Drug: A Systematic Review

Abstract: Background. Kampo medicines are traditional herbal medicines which have been approved for medicinal use by the Japanese Ministry of Health and Welfare and are currently being used more and more, often in combination with Western drugs. Thus, the need for investigation of interactions between Kampo medicines and Western drugs is now widely recognized. Aim. To summarize the effects and drug interactions of rikkunshito, a Kampo medicine often prescribed for upper gastrointestinal disorders and anorexia. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…These standardized operational procedures provoke exemplary way on careful monitoring of drug induced adverse events and also to formulate the risk-benefit ratio determination in clinical trial programme. 23 In acute toxicity study, there was no mortality up to a maximum dose of 2000 mg/kg body weight of Vishasanjeevi after per oral administration. The changes in body weight and other Clinical signs like skin color change, fecal consistency, gait analysis, urine analysis, sensory responses, animal behavior abnormalities, neuromuscular coordination have been used as an indicator of adverse effect.…”
Section: Discussionmentioning
confidence: 88%
“…These standardized operational procedures provoke exemplary way on careful monitoring of drug induced adverse events and also to formulate the risk-benefit ratio determination in clinical trial programme. 23 In acute toxicity study, there was no mortality up to a maximum dose of 2000 mg/kg body weight of Vishasanjeevi after per oral administration. The changes in body weight and other Clinical signs like skin color change, fecal consistency, gait analysis, urine analysis, sensory responses, animal behavior abnormalities, neuromuscular coordination have been used as an indicator of adverse effect.…”
Section: Discussionmentioning
confidence: 88%
“…YGJT has widely been used to treat dyspeptic symptom of upper gastrointestinal diseases including FD in clinical practice in Korea, Japan, and China [810, 12]. A few animal and human studies have demonstrated that YGJT is effective on symptoms of FD.…”
Section: Discussionmentioning
confidence: 99%
“…Yukgunja-tang (YGJT; Rikkunshito in Kampo Medicine; Liu Jun Zi Tang in Traditional Chinese Medicine) is a herbal medicine comprising eight herbs; it is used to treat FD and relieve upper gastrointestinal symptoms, including dyspepsia, epigastric discomfort, and anorexia, in clinical practice in Korea, Japan, China, and other Asian areas [811]. In animal studies, YGJT improves relaxation of the gastric fundus, which maintains gastric storage capacity, and enhances gastric antral peristalsis, which facilitates stomach emptying.…”
Section: Introductionmentioning
confidence: 99%
“…15 Because Kampo formulas are of high quality and contain standardized ingredients, recently, their pharmacologic actions have begun to be studied at the molecular level. [16][17][18][19][20] The underlying mechanisms of the proliferative effect of HJG on C2C12 cells and the active ingredient(s) for this effect are currently unknown. Because HJG consists of eight herbs and contains many ingredients, further studies are necessary to clarify the active components at the molecular level.…”
Section: Discussionmentioning
confidence: 99%